Clinical Multiteam System Composition and Complexity Among Newly Diagnosed Early-Stage Breast, Colorectal, and Lung Cancer Patients With Multiple Chronic Conditions: A SEER-Medicare Analysis. Issue 1 (6th December 2022) - Doose, Michelle; Verhoeven, Dana; Sanchez, Janeth I.; McGee-Avila, Jennifer K.; Chollette, Veronica; Weaver, Sallie J.
Abstract : PURPOSE: Sixty percent of adults have multiple chronic conditions at cancer diagnosis. These patients may require a multidisciplinary clinical team-of-teams, or a multiteam system (MTS), of high-complexity involving multiple specialists and primary care, who, ideally, coordinate clinical responsibilities, share information, and align clinical decisions to ensure comprehensive care needs are managed. However, insights examining MTS composition and complexity among individuals with cancer and comorbidities at diagnosis using US population-level data are limited. METHODS: Using SEER-Medicare data (2006-2016), we identified newly diagnosed patients with breast, colorectal, or lung cancer who had a codiagnosis of cardiopulmonary disease and/or diabetes (n = 75, 201). Zaccaro's theory-based classification of MTSs was used to categorize clinical MTS complexity in the 4 months following cancer diagnosis: high-complexity (≥ 4 clinicians from ≥ 2 specialties) and low-complexity (1-3 clinicians from 1-2 specialties). We describe the proportions of patients with different MTS compositions and quantify the incidence of high-complexity MTS care by patient groups. RESULTS: The most common MTS composition was oncology with primary care (37%). Half (50.3%) received high-complexity MTS care. The incidence of high-complexity MTS care for non-Hispanic Black and Hispanic patients with cancer was 6.7% (95% CI, −8.0 to −5.3) and 4.7% (95% CI, −6.3 to −3.0) lower than non-Hispanic White patients with cancer; 13.1% (95% CI, −14.1 to −12.2) lower for rural residents compared with urban; 10.4% (95% CI, −11.2 to −9.5) lower for dual Medicaid-Medicare beneficiaries compared with Medicare-only; and 16.6% (95% CI, −17.5 to −15.8) lower for colorectal compared with breast cancer. CONCLUSION: Incidence differences of high-complexity MTS care were observed among cancer patients with multiple chronic conditions from underserved populations. The results highlight the need to further understand the effects of and mechanisms through which care team composition, complexity, and functioning affect care quality and outcomes.